Regional Disparity and Environmental Implications in Himachal Pradesh A Case of Lowe Himachal Region Final Project Report - Planning Commission (Planning Commission, 2004)
Never before in the past, the man-environment relationship which is so precariously balanced, has come to be questioned as it is today. The problem in the third world countries especially in the environmentally sensitive and ecologically vulnerable areas has been exacerbated due to present style of development which has no indigenous roots.
Planning Commission (SER) Government of India
Planning Commission (SER) Government of India